Influence of the Draining Lymph Nodes and Organized Lymphoid Tissue Microarchitecture on Susceptibility to Intradermal Trypanosoma brucei Infection - Alfituri, Omar A.; Bradford, Barry M.; Paxton, Edith; Morrison, Liam J.; Mabbott, Neil A. (Frontiers in Immunology, 2020)
Infection of the mammalian host with African trypanosomes begins when the tsetse fly vector injects the parasites into the skin dermis during blood feeding. After injection into the skin, trypanosomes first accumulate in the draining lymph node before disseminating systemically. Whether this early accumulation within the draining lymph node is important for the trypanosomes to establish infection was not known. Lymphotoxin-β-deficient mice (LTβ−/− mice) lack most secondary lymphoid tissues, but retain the spleen and mesenteric lymph nodes. These mice were used to test the hypothesis that the establishment of infection after intradermal (ID) T. brucei infection would be impeded in the absence of the skin draining lymph nodes. However, LTβ−/− mice revealed greater susceptibility to ID T. brucei infection than wild-type mice, indicating that the early accumulation of the trypanosomes in the draining lymph nodes was not essential to establish systemic infection. Although LTβ−/− mice were able to control the first parasitemia wave as effectively as wild-type mice, they were unable to control subsequent parasitemia waves. LTβ−/− mice also lack organized B cell follicles and germinal centers within their remaining secondary lymphoid tissues. As a consequence, LTβ−/− mice have impaired immunoglobulin (Ig) isotype class-switching responses. When the disturbed microarchitecture of the B cell follicles in the spleens of LTβ−/− mice was restored by reconstitution with wild-type bone marrow, their susceptibility to ID T. brucei infection was similar to that of wild-type control mice. This effect coincided with the ability to produce significant serum levels of Ig isotype class-switched parasite-specific antibodies. Thus, our data suggest that organized splenic microarchitecture and the production of parasite-specific Ig isotype class-switched antibodies are essential for the control of ID African trypanosome infections.